Analisis Sensitivitas Metode Simple Multi Attribute Rating Technique Terhadap Pembobotan Analytic Hierarchy Process - Richa Dwi Kusmiyanti; Mustakim Mustakim (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2016)
At this time the data development of oil palm in Riau Province can only be seen from the  data  published  by  the  Central  Statistics  Agency  (BPS)  both  hardcopy  and  softcopy, presented statistically. BPS does not provide data analysis of palm oil that can be used by the Government to support the decision-making process. One technique decision support in policy analysis used in this research is Simple Multi-Attribute Rating Technique (SMART). In determining the weighting method SMART weighting technique is usually used directly. Value weight  to direct  weighting of  each criterion  is  given  in accordance  with the needs of  the subjective nature so that it is  less effective. However, in previous studies determining the weighting can be done with other techniques one of which is the Analytic Hierarchy Process (AHP). AHP is a decision support modeling that describes the problem of complex multi-criteria into a hierarchy. In AHP there is a value decision called Eigen. The eigen value obtained from Comparing pairs and are objective criteria that is substituted as the value of the weight on the SMART  method.  Results  of  ranking  using  the  SMART  method  of  direct  weighting  value sensitivity of 0.5103, while the AHP SMART have the sensitivity value of 0.0274. This indicates that the SMART AHP is a method of weighting the best because it has the smallest sensitivity. Keywords: Analytic Hierarchy Process, eigen, palm oil, Simple Multi-Attribute Rating Technique, weighting